Preparation process and application of functionalized polylactic acid fiber

By blending the silver nanoclusters supported by chitosan-hydrazide Schiff base copolymer with polylactic acid electrospinning, the problem of polylactic fiber lacking antibacterial properties and hydrophilicity is solved, the preparation of functionalized fibers is realized, and its antibacterial properties and hydrophilicity is significantly improved, and its application field is expanded.

CN118127660BActive Publication Date: 2025-03-21SHANGHAI ZHUOYE ELECTROMECHANICAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410307058.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-10-26
Filing Date
2024-03-18
Publication Date
2025-03-21
Estimated Expiration
2044-03-18

AI Technical Summary

Technical Problem

The existing polylactic fiber lacks antibacterial properties and hydrophilicity, which limits its application in the fields of medical supplies and biological tissue engineering. At the same time, nanosilver antibacterial agents are prone to agglomeration in polymer materials, affecting their stability and effects.

Method used

The material loaded with silver nanoclusters was prepared using chitosan-hydrazide Schiff base copolymer as the template agent, and electrospinned with polylactic acid to form functionalized polylactic fibers with antibacterial properties and improved hydrophilicity.

Benefits of technology

The antibacterial properties of polylactic fibers are significantly improved through uniformly dispersed silver nanoclusters, and their hydrophilicity is improved by increasing hydrophilic groups, giving them broad application prospects in the fields of antibacterial materials, medical and health care, and biological tissue engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004746195370000021
    Figure BDA0004746195370000021
  • Figure BDA0004746195370000031
    Figure BDA0004746195370000031
  • Figure BDA0004746195370000071
    Figure BDA0004746195370000071
Patent Text Reader

Abstract

The invention relates to the technical field of polylactic acid, and discloses a preparation process and application of functionalized polylactic acid fiber. The chitosan-hydrazide Schiff base copolymer template agent contains abundant hydrazide Schiff base structure and hydroxyl group, which can react with Ag + To coordinate and complex Ag + The silver nanoclusters are uniformly loaded into the template, and then reduced by ultraviolet light to generate uniformly dispersed and highly stable silver nanoclusters in the template; finally, they are electrospun by blending with polylactic acid to obtain functionalized polylactic acid fibers with antibacterial effects. The silver nanoclusters have a small particle size, a large specific surface area, and are evenly dispersed and not easy to agglomerate. They can fully contact with bacteria and other microorganisms, significantly improving the antibacterial properties of polylactic acid fibers. In addition, the chitosan-hydrazide Schiff base copolymer contains hydrophilic hydroxyl groups and hydrazide Schiff base groups, which can improve the water contact angle and hydrophilicity of polylactic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polylactic acid, and in particular to a preparation process and application of functionalized polylactic acid fiber. Background Art

[0002] In recent years, countries around the world have been vigorously developing green, environmentally friendly and degradable materials, such as polylactic acid, chitosan, cyclodextrin, etc. Among them, polylactic acid has a wide source, good biocompatibility, excellent mechanical properties, and has good applications in fibers, engineering plastics, etc.; traditional polylactic acid does not have antibacterial properties, and lacks hydrophilic groups and is hydrophobic, which limits the application of polylactic acid in medical supplies, biological tissue engineering, etc.

[0003] Nanosilver antimicrobial agent is a common antimicrobial agent with fast sterilization speed, good broad spectrum, non-toxic and pollution-free. It is widely used in polymer antimicrobial materials. However, nanosilver antimicrobial agent has the problem of easy agglomeration in polymer materials. The particle size of silver nanoclusters is between that of silver atoms and silver nanoparticles. It has the advantages of large specific surface area, no drug resistance, good biocompatibility, low dosage, etc., and has broad application prospects in antimicrobial materials.

[0004] Using polymers as templates to prepare silver nanocluster antibacterial agents with good dispersibility, high stability and small particle size is a research hotspot. The document "Synthesis of Silver Nanoclusters Composited with Carboxylated Cyclodextrin and Test of Its Antibacterial Ability" reported that carboxymethyl-β-cyclodextrin was used as a template to prepare silver nanoclusters with excellent antibacterial properties. The present invention uses chitosan-hydrazide Schiff base copolymer as a template to prepare chitosan-hydrazide Schiff base copolymer-loaded silver nanoclusters, aiming to improve the antibacterial properties and hydrophilicity of polylactic acid fibers. Summary of the invention

[0005] 1. Technical issues to be solved

[0006] In view of the shortcomings of the prior art, the present invention provides a chitosan-hydrazide Schiff base copolymer loaded with silver nanoclusters, which solves the problems that the nanosilver antibacterial agent is easy to agglomerate and the polylactic acid fiber has no antibacterial property.

[0007] (II) Technical solution

[0008] A preparation process of functionalized polylactic acid fiber: dissolving polylactic acid in dichloromethane to prepare a polylactic acid solution with a mass fraction of 50-100 g / L; adding chitosan-hydrazide Schiff base copolymer loaded silver nanoclusters into N,N-dimethylformamide solvent to prepare a silver nanocluster solution with a mass fraction of 0.05-0.5 g / L; dripping the silver nanocluster solution into the polylactic acid solution, and controlling the volume ratio of the polylactic acid solution to the silver nanocluster solution to be 3-5:1. Prepare a spinning solution, then pour the solution into a syringe, and spin it through an electrospinning machine, the spinning rate is 0.4-1 mL / h, the receiving distance is adjusted to 15-20 cm, and the receiving roller speed is 200-500 r / min, to obtain functionalized polylactic acid fiber with antibacterial effect.

[0009] Preferably, the preparation process of the chitosan-hydrazide Schiff base copolymer loaded with silver nanoclusters is:

[0010] S1. Add acetic acid solution, glutaraldehyde and 3-hydroxyglutaric hydrazide to tetrahydrofuran, reflux at 60-80°C for 18-36h, then add chitosan and water, stir and react for 2-6h, add sodium bicarbonate and stir until precipitate is precipitated, filter, and wash with ethanol to obtain chitosan-hydrazide Schiff base copolymer; the reaction route is:

[0011]

[0012] S2. Add chitosan-hydrazide Schiff base copolymer into water to prepare a copolymer solution, stir to dissolve, then add silver nitrate, stir for 6-12 hours, irradiate under ultraviolet light for 2-3 hours, concentrate the solvent, wash with ethanol, and obtain chitosan-hydrazide Schiff base copolymer loaded with silver nanoclusters.

[0013] Preferably, the mass ratio of glutaraldehyde, 3-hydroxyglutaric hydrazide and chitosan is 60-90:100:15-40.

[0014] Preferably, the mass fraction of the copolymer solution is 1-15 g / L.

[0015] Preferably, the mass ratio of the chitosan-hydrazide Schiff base copolymer to silver nitrate is 1:5-20.

[0016] Preferably, the preparation process of 3-hydroxyglutaric acid hydrazide is: adding 3-hydroxyglutaric acid diethyl ester and hydrazine hydrate in a mass ratio of 1:5-8 to ethanol, reacting at a temperature of 25-40° C. for 4-10 hours, concentrating, and washing with petroleum ether to obtain 3-hydroxyglutaric acid hydrazide; the reaction formula is:

[0017]

[0018] (III) Beneficial technical effects

[0019] The present invention uses 3-hydroxyglutaric hydrazide containing hydroxyl groups to carry out Schiff base polymerization reaction in glutaraldehyde, and then reacts with chitosan to obtain chitosan-hydrazide Schiff base copolymer; the copolymer contains abundant hydrazide Schiff base structure and hydroxyl groups, which can react with Ag + The chitosan-hydrazide Schiff base copolymer can be used as a polymer template to make Ag + It is evenly loaded into the template and then reduced by ultraviolet light to generate uniformly dispersed and highly stable silver nanoclusters in the template; finally, the chitosan-hydrazide Schiff base copolymer loaded with silver nanoclusters is electrospun together with polylactic acid to obtain functionalized polylactic acid fibers with antibacterial effect.

[0020] Silver nanoclusters have small particle size, large specific surface area, and are evenly dispersed and not easy to agglomerate. They can fully contact with bacteria and other microorganisms, significantly improving the antibacterial properties of polylactic acid fibers. In addition, chitosan-hydrazide Schiff base copolymers contain hydrophilic hydroxyl groups and hydrazide Schiff base groups, which can improve the water contact angle and hydrophilicity of polylactic acid; it has broad application prospects in antibacterial materials, medical and health care, and biological tissue engineering. DETAILED DESCRIPTION

[0021] Example 1

[0022] To 40 mL of ethanol, 3 g of diethyl 3-hydroxyglutarate and 20 g of hydrazine hydrate were added, the mixture was reacted at 30° C. for 8 h, concentrated, and washed with petroleum ether to obtain 3-hydroxyglutaric hydrazide.

[0023] To 20 mL of tetrahydrofuran, 0.3 mL of glacial acetic acid solution, 1.2 g of glutaraldehyde and 2 g of 3-hydroxyglutaric hydrazide were added, and the mixture was refluxed at 70°C for 18 h. Then, 0.8 g of chitosan and water were added, and the reaction was stirred for 6 h. Sodium bicarbonate was added and stirred until a precipitate was precipitated. The mixture was filtered and washed with ethanol to obtain a chitosan-hydrazide Schiff base copolymer.

[0024] 2 g of chitosan-hydrazide Schiff base copolymer was added to water to prepare a copolymer solution with a mass fraction of 1 g / L, and the solution was dissolved by stirring. Then 10 g of silver nitrate was added, stirred for 8 h, irradiated under ultraviolet light for 2 h, the solvent was concentrated, and washed with ethanol to obtain chitosan-hydrazide Schiff base copolymer-loaded silver nanoclusters.

[0025] Polylactic acid was dissolved in dichloromethane to prepare 60 mL of a polylactic acid solution with a mass fraction of 100 g / L; chitosan-hydrazide Schiff base copolymer loaded silver nanoclusters was added to N,N-dimethylformamide solvent to prepare 20 mL of a silver nanocluster solution with a mass fraction of 0.05 g / L; the silver nanocluster solution was dropped into the polylactic acid solution to prepare a spinning solution; the solution was then poured into a syringe and spun through an electrospinning machine at a spinning rate of 0.8 mL / h, the receiving distance was adjusted to 20 cm, and the receiving roller speed was 400 r / min to obtain functionalized polylactic acid fibers with antibacterial effect.

[0026] Example 2

[0027] To 30 mL of ethanol, 3 g of diethyl 3-hydroxyglutarate and 18 g of hydrazine hydrate were added, the mixture was reacted at 30° C. for 4 h, concentrated, and washed with petroleum ether to obtain 3-hydroxyglutaric hydrazide.

[0028] To 50 mL of tetrahydrofuran, add 0.8 mL of glacial acetic acid solution, 1.2 g of glutaraldehyde and 2 g of 3-hydroxyglutaric hydrazide, reflux at 60 ° C for 24 h, then add 0.3 g of chitosan and water, stir and react for 4 h, add sodium bicarbonate and stir until a precipitate is precipitated, filter, and wash with ethanol to obtain a chitosan-hydrazide Schiff base copolymer.

[0029] 2 g of chitosan-hydrazide Schiff base copolymer was added to water to prepare a copolymer solution with a mass fraction of 3 g / L, and the solution was dissolved by stirring. Then 15 g of silver nitrate was added, stirred for 8 h, irradiated under ultraviolet light for 3 h, the solvent was concentrated, and washed with ethanol to obtain chitosan-hydrazide Schiff base copolymer-loaded silver nanoclusters.

[0030] Polylactic acid was dissolved in dichloromethane to prepare 80 mL of a polylactic acid solution with a mass fraction of 70 g / L; chitosan-hydrazide Schiff base copolymer loaded silver nanoclusters was added to N,N-dimethylformamide solvent to prepare 20 mL of a silver nanocluster solution with a mass fraction of 0.15 g / L; the silver nanocluster solution was dropped into the polylactic acid solution to prepare a spinning solution; the solution was then poured into a syringe and spun through an electrospinning machine at a spinning rate of 1 mL / h, the receiving distance was adjusted to 20 cm, and the receiving roller speed was 200 r / min to obtain functionalized polylactic acid fibers with antibacterial effect.

[0031] Example 3

[0032] To 40 mL of ethanol, 3 g of diethyl 3-hydroxyglutarate and 24 g of hydrazine hydrate were added, and the mixture was reacted at 25° C. for 10 h. The mixture was concentrated and washed with petroleum ether to obtain 3-hydroxyglutaric hydrazide.

[0033] To 50 mL of tetrahydrofuran, add 0.3 mL of glacial acetic acid solution, 1.8 g of glutaraldehyde and 2 g of 3-hydroxyglutaric hydrazide, reflux at 70 ° C for 24 h, then add 0.8 g of chitosan and water, stir and react for 4 h, add sodium bicarbonate and stir until a precipitate is precipitated, filter, and wash with ethanol to obtain a chitosan-hydrazide Schiff base copolymer.

[0034] 2 g of chitosan-hydrazide Schiff base copolymer was added to water to prepare a copolymer solution with a mass fraction of 8 g / L, and the solution was dissolved by stirring. Then 25 g of silver nitrate was added, stirred for 12 h, irradiated under ultraviolet light for 2 h, the solvent was concentrated, and washed with ethanol to obtain chitosan-hydrazide Schiff base copolymer-loaded silver nanoclusters.

[0035] Polylactic acid was dissolved in dichloromethane to prepare 100 mL of a polylactic acid solution with a mass fraction of 50 g / L; chitosan-hydrazide Schiff base copolymer loaded silver nanoclusters was added to N,N-dimethylformamide solvent to prepare 20 mL of a silver nanocluster solution with a mass fraction of 0.3 g / L; the silver nanocluster solution was dropped into the polylactic acid solution to prepare a spinning solution; the solution was then poured into a syringe and spun through an electrospinning machine at a spinning rate of 0.6 mL / h. The receiving distance was adjusted to 15 cm and the receiving roller speed was 400 r / min to obtain functionalized polylactic acid fibers with antibacterial effect.

[0036] Example 4

[0037] To 30 mL of ethanol, 3 g of diethyl 3-hydroxyglutarate and 15 g of hydrazine hydrate were added, the mixture was reacted at 30° C. for 4 h, concentrated, and washed with petroleum ether to obtain 3-hydroxyglutaric hydrazide.

[0038] To 50 mL of tetrahydrofuran, add 0.5 mL of glacial acetic acid solution, 1.2 g of glutaraldehyde and 2 g of 3-hydroxyglutaric hydrazide, reflux at 60 ° C for 36 h, then add 0.3 g of chitosan and water, stir and react for 4 h, add sodium bicarbonate and stir until a precipitate is precipitated, filter, and wash with ethanol to obtain a chitosan-hydrazide Schiff base copolymer.

[0039] 2 g of chitosan-hydrazide Schiff base copolymer was added to water to prepare a copolymer solution with a mass fraction of 12 g / L, and the solution was dissolved by stirring. Then 30 g of silver nitrate was added, stirred for 12 h, irradiated under ultraviolet light for 3 h, the solvent was concentrated, and washed with ethanol to obtain chitosan-hydrazide Schiff base copolymer-loaded silver nanoclusters.

[0040] Polylactic acid was dissolved in dichloromethane to prepare 100 mL of a polylactic acid solution with a mass fraction of 50 g / L; chitosan-hydrazide Schiff base copolymer loaded silver nanoclusters was added to N,N-dimethylformamide solvent to prepare 20 mL of a silver nanocluster solution with a mass fraction of 0.4 g / L; the silver nanocluster solution was dropped into the polylactic acid solution to prepare a spinning solution; the solution was then poured into a syringe and spun through an electrospinning machine at a spinning rate of 0.4 mL / h. The receiving distance was adjusted to 18 cm and the receiving roller speed was 400 r / min to obtain functionalized polylactic acid fibers with antibacterial effect.

[0041] Example 5

[0042] 3 g of diethyl 3-hydroxyglutarate and 24 g of hydrazine hydrate were added to 40 mL of ethanol, reacted at 40° C. for 8 h, concentrated, and washed with petroleum ether to obtain 3-hydroxyglutaric hydrazide.

[0043] To 50 mL of tetrahydrofuran, add 0.8 mL of glacial acetic acid solution, 1.8 g of glutaraldehyde and 2 g of 3-hydroxyglutaric hydrazide, reflux at 70 ° C for 18 h, then add 0.4 g of chitosan and water, stir and react for 4 h, add sodium bicarbonate and stir until a precipitate is precipitated, filter, and wash with ethanol to obtain a chitosan-hydrazide Schiff base copolymer.

[0044] 2 g of chitosan-hydrazide Schiff base copolymer was added to water to prepare a copolymer solution with a mass fraction of 15 g / L, and the solution was dissolved by stirring. Then 40 g of silver nitrate was added, stirred for 12 h, irradiated under ultraviolet light for 3 h, the solvent was concentrated, and washed with ethanol to obtain chitosan-hydrazide Schiff base copolymer-loaded silver nanoclusters.

[0045] Polylactic acid was dissolved in dichloromethane to prepare 80 mL of a polylactic acid solution with a mass fraction of 70 g / L; chitosan-hydrazide Schiff base copolymer loaded silver nanoclusters was added to N,N-dimethylformamide solvent to prepare 20 mL of a silver nanocluster solution with a mass fraction of 0.5 g / L; the silver nanocluster solution was dropped into the polylactic acid solution to prepare a spinning solution; the solution was then poured into a syringe and spun through an electrospinning machine at a spinning rate of 1 mL / h, the receiving distance was adjusted to 15 cm, and the receiving roller speed was 200 r / min to obtain functionalized polylactic acid fibers with antibacterial effect.

[0046] Comparative Example 1

[0047] The polylactic acid was dissolved in dichloromethane to prepare 60 mL of a polylactic acid solution with a mass fraction of 100 g / L; the chitosan-hydrazide Schiff base copolymer prepared in Example 1 was added to an N,N-dimethylformamide solvent to prepare 20 mL of a solution with a mass fraction of 0.05 g / L, and the solution was added dropwise to the polylactic acid solution to prepare a spinning solution, and then the solution was poured into a syringe and spun by an electrospinning machine at a spinning rate of 0.4 mL / h. The receiving distance was adjusted to 18 cm and the receiving roller speed was 500 r / min to obtain polylactic acid fibers.

[0048] Comparative Example 2

[0049] Polylactic acid was dissolved in dichloromethane to prepare 60 mL of a polylactic acid solution with a mass fraction of 100 g / L. The solution was poured into a syringe and spun through an electrospinning machine at a spinning rate of 0.4 mL / h. The receiving distance was adjusted to 18 cm and the receiving roller speed was 500 r / min to obtain polylactic acid fibers.

[0050] The water contact angle of PLA fiber was tested by an optical contact angle tester.

[0051]

[0052]

[0053] In Example 1-5, polylactic acid and chitosan-hydrazide Schiff base copolymer loaded with silver nanoclusters were blended and electrospun. As the mass fraction of chitosan-hydrazide Schiff base copolymer loaded with silver nanoclusters in the silver nanocluster solution increased, the water contact angle of the prepared polylactic acid fiber became smaller and smaller, and the hydrophilicity became better and better.

[0054] Colony experiment: Add 100 μL of E. coli seed solution to 10 mL of nutrient broth liquid culture medium, mix well, and culture in a shaker at 37°C for 12 h for activation.

[0055] 200 μL of activated bacterial solution, 20 mL of PBS buffer solution, 3 mL of nutrient broth liquid culture medium and 1 g of polylactic acid fiber were added to the test tube and shaken for different times as the experimental group; the blank control group did not add polylactic acid fiber; after shaking, the culture solution was removed and diluted 10 6 Then, 200 μL of the diluted bacterial solution was applied to the surface of the agar medium and cultured in a constant temperature incubator at 37°C for 24 h. The bacterial count (CFU / mL) was counted and the antibacterial rate Q was calculated.

[0056] Q = (AB) / A×100%. A is the bacterial count (CFU / mL) of the blank control group, and B is the bacterial count (CFU / mL) of the experimental group.

[0057]

[0058] In Examples 1-5, as the mass fraction of the silver nanoclusters loaded by the chitosan-hydrazide Schiff base copolymer in the silver nanocluster solution increases, the antibacterial performance of the obtained polylactic acid fiber becomes stronger and stronger. When the oscillation contact is 30 minutes, the antibacterial rate of Escherichia coli in Examples 4 and 5 reaches 99.99%. Comparative Example 1 is spun with only polylactic acid and chitosan-hydrazide Schiff base copolymer, without silver nanoclusters, and has poor antibacterial performance. The antibacterial rate is as high as 73.92% after 90 minutes of oscillation contact; Comparative Example 2 is ordinary polylactic acid fiber, which basically has no antibacterial performance.

[0059] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. A process for preparing functionalized polylactic acid fiber, characterized in that: The preparation process comprises the following steps: dissolving polylactic acid in dichloromethane to prepare a polylactic acid solution with a mass fraction of 50-100 g / L; adding chitosan-hydrazide Schiff base copolymer loaded silver nanoclusters into N,N-dimethylformamide solvent to prepare a silver nanocluster solution with a mass fraction of 0.05-0.5 g / L; dripping the silver nanocluster solution into the polylactic acid solution, controlling the volume ratio of the polylactic acid solution to the silver nanocluster solution to be 3-5:1, preparing a spinning solution, then pouring the solution into a syringe, spinning through an electrostatic spinning machine, the spinning rate being 0.4-1 mL / h, adjusting the receiving distance to be 15-20 cm, and the receiving roller speed to be 200-500 r / min, to obtain functionalized polylactic acid fibers with antibacterial effects.

2. The process for preparing functionalized polylactic acid fiber according to claim 1, characterized in that: The preparation process of the chitosan-hydrazide Schiff base copolymer loaded with silver nanoclusters is as follows: S1, adding acetic acid solution, glutaraldehyde and 3-hydroxyglutaric hydrazide to tetrahydrofuran, reflux at a temperature of 60-80°C for 18-36h, then adding chitosan and water, stirring and reacting for 2-6h, adding sodium bicarbonate and stirring until a precipitate is precipitated, filtering, and washing with ethanol to obtain a chitosan-hydrazide Schiff base copolymer; S2. Add chitosan-hydrazide Schiff base copolymer into water to prepare a copolymer solution with a mass fraction of 1-15 g / L, stir to dissolve, then add silver nitrate, stir for 6-12 hours, irradiate under ultraviolet light for 2-3 hours, concentrate the solvent, wash with ethanol, and obtain chitosan-hydrazide Schiff base copolymer loaded with silver nanoclusters.

3. The process for preparing functionalized polylactic acid fiber according to claim 2, characterized in that: The mass ratio of the glutaraldehyde, 3-hydroxyglutaric hydrazide and chitosan is 60-90:100:15-40.

4. The process for preparing functionalized polylactic acid fiber according to claim 2, characterized in that: The mass ratio of the chitosan-hydrazide Schiff base copolymer to silver nitrate is 1:5-20.

5. The process for preparing functionalized polylactic acid fiber according to claim 2, characterized in that: The preparation process of 3-hydroxyglutaric acid hydrazide is as follows: adding 3-hydroxyglutaric acid diethyl ester and hydrazine hydrate in a mass ratio of 1:5-8 to ethanol, reacting at a temperature of 25-40° C. for 4-10 hours, concentrating, and washing with petroleum ether to obtain 3-hydroxyglutaric acid hydrazide.

Citation Information

Patent Citations

  • Nano-silver antibacterial composite decorated by modified chitosan, preparing method and application

    CN104128602A

  • Thiolated chitosan-based nanosilver in situ reduced antibacterial cotton fabric

    CN109487554A